Avaliação do papel da faixa de domínio na redução de vibrações produzidas por trens em áreas urbanas - Chaves, Gianna Vanessa de Assis (2008)
Currently, urban centres are more and more subject to vibration induced by traffic, because of its increasing volume. Among the vibration effects are damage to buildings. In this study, the effects of the vibration produced by suburban trains in buildings was investigated, by taking a railway line with mixed passenger and cargo traffic as a (typical) case study. Measurements were taken, aiming to identify the vibration levels in buildings adjacent to the railway line and which presented visible cracks in their surfaces. The results obtained revealed that vibration levels produced by passenger trains were below the limits which could potentially cause damage. However, simulations performed in order to estimate the vibration levels induced by freight trains evidenced the occurrence of levels greater than those acceptable for the type of buildings investigated.